Phenotypes and genetic etiology of spontaneous polycystic kidney and liver disease in cynomolgus monkey - Wu, Ruo; Bai, Bing; Li, Feng; Bai, Raoxian; Zhuo, Yan; Zhu, Zhengna; Jia, Rongfang; Li, Shangang; Chen, Yongchang; Lan, Xiaoping (Frontiers in Veterinary Science, 2023)
Polycystic kidney disease (PKD) is a common autosomal dominant or recessive genetic disorder, often with or without polycystic liver disease (PLD). Many cases in animals of PKD have been reported already. However, little is known about the disease-causing genes that cause PKD in animals. In this study, we described the clinical phenotypes of polycystic kidney disease in two spontaneously aged cynomolgus monkeys and explored the genetic etiology using Whole-genome sequencing (WGS). Ultrasonic diagnosis, and pathological dissection to analyze and diagnose PKD/PLD. The results indicated that the kidneys of the two monkeys had varying degrees of cystic changes in anatomical specimens, and the renal cortex was thinned and accompanied by fluid accumulation. As for hepatopathy, inflammatory cell infiltration, cystic effusion, hepatocyte steatosis, and pseudo-lobular were found. Based on WGS results, the variants of PKD1:(XM_015442355: c.1144G>C p. E382Q) and GANAB: (NM_001285075.1: c.2708T>C/p. V903A) were predicted to be likely pathogenic heterozygous mutations in PKD and PLD-affected monkeys. Our study demonstrates that the cynomolgus monkeys’ PKD and PLD phenotypes are very similar to those in humans, and probably caused by pathogenic genes homologous to humans, cynomolgus monkeys can be used as the most appropriate animal model for human PKD pathogenesis research and therapeutic drug screening.